Hubungan Work Overload dengan Stres Kerja pada Pengemudi Ojek Online Generasi Z - Annisa Warastri; Muhammad Raja' Firdaus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
With the economic downturn and reduced employment opportunities in the formal sector, many generation Z have turned to online motorcycle taxis with uncertain working hours and high work stress. This research aims to see the relationship between work overload and work stress experienced by generation Z online motorcycle taxi drivers. This research uses a correlational quantitative method with a sample of 100 people with criteria of 17-29 years and working in DIY. The scales used in this research are the work overload scale with a reliability of 0.721 and the work stress scale with a reliability of 0.764. Hypothesis testing was carried out using the Pearson product moment test and with a value of 0.216. The categorization results showed that generation Z online motorcycle taxis experienced moderate levels of work stress and work overload.